Salivary Reduction of Dietary Nitrate - Clodfelter, William Howard Craig (Wake Forest University, 2015)
Nitric oxide (NO) is an important cellular signaling molecule known mostly for its vasodilatative effects. Nitrate (NO3-) acts as an important NO source through reductive physiological pathways. Basal plasma NO3- levels are a sum of the oxidation of endogenous NO and ingested dietary NO3-. Approximately 25% of dietary NO3- is recovered by the salivary glands and concentrated up to 20-fold in saliva. Humans possess symbiotic NO3- reductase activity from the anaerobic bacteria (Actinomyces and Veillonella) species found in the tongue’s cleft. Preliminary genomic analyses of these species indicate the lack of nitrite (NO2-) reductase ortholog genes suggesting dissimilatory NO3- reduction. The goal of Aim 1 of this research was to investigate and fully characterize the reduction of dietary NO3- to reduced nitrogen oxides in the oral cavity.
Keywords: Dietary Nitrate; Nitrate; Nitric Oxide; Nitrite; Nitrogen Oxide; Saliva